Oxygen uptake rates have contrasting responses to temperature in the root meristem and elongation zone. Issue 2 (18th April 2022) - Zimmermann, Maura J.; Bose, Jayakumar; Kramer, Eric M.; Atkin, Owen K.; Tyerman, Stephen D.; Baskin, Tobias I.
Abstract: Growing at either 15 or 25°C, roots of Arabidopsis thaliana, Columbia accession, produce cells at the same rate and have growth zones of the same length. To determine whether this constancy is related to energetics, we measured oxygen uptake by means of a vibrating oxygen‐selective electrode. Concomitantly, the spatial distribution of elongation was measured kinematically, delineating meristem and elongation zone. All seedlings were germinated, grown, and measured at a given temperature (15 or 25°C). Columbia was compared to lines where cell production rate roughly doubles between 15 and 25°C: Landsberg and two Columbia mutants, er‐105 and ahk3‐3 . For all genotypes and temperatures, oxygen uptake rate at any position was highest at the root cap, where mitochondrial density was maximal, based on the fluorescence of a reporter. Uptake rate declined through the meristem to plateau within the elongation zone. For oxygen uptake rate integrated over a zone, the meristem had steady‐state Q 10 values ranging from 0.7 to 2.1; by contrast, the elongation zone had values ranging from 2.6 to 3.3, implying that this zone exerts a greater respiratory demand. These results highlight a substantial energy consumption by the root cap, perhaps helpful for maintaining hypoxia in stem cells, and suggest that rapid elongation is metabolically more costly than is cell division.